Production of ligninolytic enzymes by white rot fungi on lignocellulosic wastes using novel pretreatments - Pandey, A. K.; Vishwakarma, S. K.; Srivastava, A. K.; Pandey, V. K.; Agrawal, S.; Singh, M. P. (Cellular and Molecular Biology, 2014)
Production of extracellular ligninolytic enzymes (laccase and polyphenol oxidase) secreted by three species of white rot fungi (Pleurotus florida, P. flabellatus and P. sajor-caju) under in vivo condition was studied on two lignocellulosic substrates i.e., paddy straw and wheat straw. These lignocellulosic substrates were treated with neem (Azadirachta indica) oil and ashoka (Saraca indica) leaves extract. Between the two lignocellulosic substrates, paddy straw pretreated with neem oil supported maximum activity of laccase and polyphenol oxidase (PPO). The activities of both the enzymes were low on the 5th day of cultivation which increased on the 10th day and reached at peak on the 15th day. Thereafter, there was continuous decrease in the enzymatic activity. Among the three species, P. flabellatus (P3) showed maximum ligninolytic enzymatic activity followed by P. florida (P2)and P. sajor-caju (P1).